Effect of intravenous dexamethasone on post-operative inflammatory sequelae after third molar surgery: A split-mouth comparative study - Singh Gurung, Utsav; Shakya Gurung, Rashmi; Bhattarai, Anjali; Jwarchan, Roshani; Bhandari, Anmol (Journal of Chitwan Medical College, 2026)
Introduction: Postoperative inflammatory sequelae following surgical removal of third molars adversely affect the quality of life for patients.  Dexamethasone is well known to suppress inflammation. As acute inflammation peaks around post-operative day 1 to 3, a single dose of parental dexamethasone (having a long half-life of 36 to 72 hours) is effective. This comparative study aims to evaluate the effect of intravenous dexamethasone on post-operative inflammatory sequelae after third molar surgery.Method: In a prospective comparative study at Nepal Medical College and Teaching Hospital, Kathmandu, Nepal, from Aug 2025 to Oct 2025, 51 patients underwent surgical extraction of bilaterally symmetrical mandibular third molars in two sessions on an outpatient basis following ethical approval. Fifty-one patients received a single dose of 8 mg intravenous dexamethasone 30 minutes before extraction at one site and normal saline as a placebo on the contralateral site. Post-operative pain, swelling, and trismus were evaluated on the first, third, and seventh post-operative days. The IBM SPSS was used to analyse data. For descriptive analysis, Mean±SD was used after confirming normality (Korov-Smirnov test) and a paired t-test for comparison of continuous variables. A p≤0.05 was considered significant.Result: Dexamethasone injection group showed significantly less pain than the control group at postoperative day 1 and less swelling on day 3. There was no statistically significant difference in mean maximal mouth opening between the two groups on any day.Conclusion: Prophylactic intravenous administration of dexamethasone was effective in reducing postoperative pain and swelling after third molar surgery.